Preparation and Characterization of Thin‐Film Nanocomposite Membrane Incorporated with MoO3 Nanoparticles with High Flux Performance for Forward Osmosis. Issue 27 (15th July 2019) - Amini, Mojtaba; Shekari, Zahra; Hosseinifard, Mojtaba; Seidi, Farzad
Abstract: In this research, thin film nanocomposite (TFN) membranes were developed using novel polyethersulfone– molybdenum oxide (PES–MoO3 ) nanocomposite substrate. The effects of MoO3 nanoparticles on the PES substrate morphologies, surface roughness, hydrophilicity, and water permeability were investigated by measuring the water contact angles, scanning electron microscope (SEM) imaging, FT‐IR spectroscopy, and atomic force microscope (AFM) analysis. The MoO3 nanoparticle modified membranes were used in the forward osmosis (FO) process with both PRO mode (the membrane active layer facing draw solution) and FO (the membrane active layer facing feed solution) mode. The results indicated enhanced water permeability of the modified membranes upon the MoO3 addition, leading to significant enhancement in the water flux and the desalination performance. Abstract : A thin‐Film nanocomposite membrane incorporated with MoO3 nanoparticles was developed with high Flux performance for forward osmosis (FO) process.